A comparative study to evaluate the effects of pre-chamber jet ignition for engine characteristics and emission formations at high speed. (1st November 2020) - Yontar, Ahmet Alper
Abstract: The pre-chamber ignition technology is a good solution that can make spark-ignition engines gradually more efficient. The novelty of the study is the testing of the pre-chamber jet ignition according to detailed air-fuel mixture range and fuel injection rates by combustion chambers. The main points in using this pre-chamber jet ignition were to observe the effect of reducing fuel consumption and emission formation. The tests were carried out for 0.80–1.80 lambda ranges and the pre-chamber injection/main chamber injection mass ratio ranges. A commercial RON 98 fuel was used at two ignition modes in tests for 5000 rpm high engine speed. At the pre-chamber jet ignition usage, the in-cylinder pressure for 1.00 lambda is overall 1.78% and 19.89% higher than the 0.80 lambda and the 1.80 lambda. The brake specific fuel consumption is about 8.67% lower than the spark-plug ignition usage at 0.80–1.20 lambda range. The HC formation is overall 8.12% lower than the spark-plug usage. The NOx formation for the spark-plug ignition is approximately 53.97% higher than the pre-chamber jet ignition usage as the temperature in-cylinder is high. The pre-chamber jet ignition was led to a much shorter flame development time and better combustion stability than the spark-plug. Highlights: Pre-chamber jet ignition effects on engine performance characteristics at high speed. Determination of jet ignition effects for air-fuel mixtures and injection rates. The tests were carried out for RON 98 fuel at 5000 rpm high engine speed. The BSFC at jet ignition is about 8.67% lower than the spark-plug ignition. The NOx for the spark-plug ignition is overall 53.97% higher than the jet ignition.